MENEGUHKAN KEMBALI KEBERAGAMAN INDONESIA - Sudarto S. (Masyarakat Indonesia, 2018)
The basic feature of democracy is diversity. So the main issue in democracy is how to manage the diversity according to the principles of equality and justice. In this regard, it is undeniable that Indonesia is a plural country with the largest Muslim population in the world. On the one hand Indonesia is in the maturation of democracy, but on the other hand Indonesia is still faced with many challenges in managing the diversity. The plurality of problems as described above is caused by the following: First, there are still many regulations produced by the state which in essence precisely complicate the management of the diversity itself. Included in this problem is the lack of protection of freedom of religion and belief by law enforcement officials. Second, the strong desire to dominate from dominant groups to smaller groups of quantities. Third, felt still fragile foundation of tolerance in society body itself. The three roots of the problem have an intercausal relationship. As a result, non-mainstream groups become victims of discrimination, especially local religious groups, which occur in a structured, widespread and systematic manner. The problem is how to rearrange the Indonesian religion according to the principles of equality and justice especially to the local religious groups of the archipelago? To answer the big question, the author uses civic pluralism approach offered by Robert W Hefner. According to Hefner, society can be called a civic pluralist, when each member throws away efforts to suppress and reduce diversity (Hefner, 2003: 195). This paper aims to offer the concept of diversity management that is expected to contribute to re-establish Indonesia's diversity.